Global, regional, and national burden of knee osteoarthritis attributable to high BMI: a systematic analysis from 1990 to 2021 and projections to 2050 - Xu, Jiaxian; Lei, Mingming; Xu, Dandan (Frontiers in Public Health, 2025)
BackgroundKnee osteoarthritis (KOA) is one of the most prevalent joint diseases globally, with high body mass index (BMI) being a major risk factor. We aimed to assess the burden of KOA attributable to high BMI across global, regional, and national levels from 1990 to 2021 and to project trends to 2050.MethodsData were obtained from the Global Health Data Exchange (GHDx) and identified using the M17 code from the International Classification of Diseases, 10th Revision (ICD-10). The analysis focused on disability-adjusted life years (DALYs) and years lived with disability (YLDs). Using R software, we calculated age-standardized rates and generated world maps to illustrate the distribution and trends. Future burden was projected using a combination of log-linear models and Bayesian inference, in line with the Global Burden of Disease (GBD) research standards. Parameters were calibrated using demographic projections from the GBD 2021 study.FindingsBetween 1990 and 2021, there was a significant increase in global DALYs and YLDs of KOA due to high BMI, with a greater burden observed in females compared with males. The most rapid increase was seen in low-middle Socio-demographic Index (SDI) countries. In 2021, the highest burden was in China, the United States, and India. Projections indicate that by 2050, global DALYs and YLDs will nearly double, with females continuing to have a higher burden than males and the highest age-standardized DALY rates in high SDI regions.InterpretationThe impact of high BMI on the burden of KOA is substantial. Future efforts should focus on individuals aged 50 years and older, females, and low-middle SDI regions for intensified health education and interventions. Promoting a healthy lifestyle, including balanced diets and increased physical activity, is essential to mitigate the future burden of KOA attributable to high BMI. Region-specific interventions are needed. For example, low-middle SDI regions, where obesity rates are rising alongside limited healthcare resources, would benefit from targeted health education programs, including weight management, physical activity promotion, and access to affordable healthcare. High SDI regions should focus on obesity prevention through policy interventions that regulate food quality and encourage physical activity.